Comparative Evaluation of Anti-inflammatory, Antipyretic and Analgesic Properties of Ixora coccinea and Mussaenda frondosa (Rubiaceae) Leaves - Bose, Sankhadip; Mandal, Sudip Kumar; Das, Purba; Nandy, Sayan; Das, Anupam; Dutta, Dibyendu; Chakraborti, Chandra; Sarkar, Dhrubajyoti; Dey, Suddhasattya (Jordan Journal of Pharmaceutical Sciences, 2020)
The present study was an attempt to establish a comparative study of anti-inflammatory, analgesic and antipyretic properties of methanol extracts of Ixora coccinea and Mussaenda frondosa leaves (Rubiaceae). In anti-inflammatory, activity the formation of edema relies upon the generation and participation of various inflammatory factors e.g. kinins and peripheral blood mononuclear cells (PBMC). These include prostaglandins, chemokines, and cytokines (interleukins). Secondly, the analgesic activity has been carried out using Eddy’s Hot plate method, Tail Flick Method and Acetic Acid induced Writhing Method in mice compared to the reference drug Diclofenac sodium. This is may be due to the stimulation of pain reduction by peripheral mechanism, achieved by inhibition of prostaglandin synthesis. For antipyretic method, pyrexia induced method was used using Brewer’s yeast where Paracetamol was used as the standard drug. Antipyretic activity is observed may be due the inhibition of prostaglandin synthesis in the region of hypothalamus of brain (CNS). It has been concluded that the methanol extract of Mussaenda frondosa was more potent in comparison to Ixora coccinea as anti-inflammatory, antipyretic and analgesic drug at the dose of 500 mg/kg body weight.